Cell Polarization and Epigenetic Status Shape the Heterogeneous Response to Type III Interferons in Intestinal Epithelial Cells - Bhushal, Sudeep; Wolfsmüller, Markus; Selvakumar, Tharini A.; Kemper, Lucas; Wirth, Dagmar; Hornef, Mathias W.; Hauser, Hansjörg; Köster, Mario (Frontiers in Immunology, 2017)
Type I and type III interferons (IFNs) are crucial components of the first line antiviral host response. While specific receptors for both IFN types exist, intracellular signaling shares the same Jak-STAT pathway. Due to its receptor expression IFN-λ responsiveness is restricted mainly to epithelial cells. Here we display IFN-stimulated gene induction at the single cell level to comparatively analyze the activities of both IFN types in intestinal epithelial cells and mini-gut organoids. Initially, we noticed that the response to both types of IFN at low concentrations is based on a single cell decision making determining the total cell intrinsic antiviral activity. We identified HDAC activity as a crucial restriction factor controlling the cell frequency of ISG induction upon IFN-λ but not IFN-β stimulation. Consistently, HDAC blockade confers antiviral activity to an elsewise non-responding subpopulation. Second, in contrast to the type I IFN system, polarization of intestinal epithelial cells strongly enhances their ability to respond to IFN-λ signaling and raises the kinetics of gene induction. Finally, we show that ISG induction in mini-gut organoids by low amounts of IFN is characterized by a scattered heterogeneous responsiveness of the epithelial cells and HDAC activity fine tunes exclusively IFN-λ activity. This study provides a comprehensive description of the differential response to type I and type III IFNs and demonstrates that cell polarization in gut epithelial cells specifically increases IFN-λ activity.